The Authority of the State Audit Board in Managing State Finances as an Effort to Prevent Corruption - Lisa Ade Candra; Achmad Ruslan; Marten Arie (Jurnal Hukum Volkgeist, 2022)
This study aims to explain the authority of BPK in examining the management and responsibilities of state finances. To explain the role of BPK in saving state finances and efforts to eradicate corruption. This research uses a normative research type, using a statutory, a conceptual and a historical approach. The types and sources of law used in this study are primary and secondary data. All of the data analyzed qualitatively and presented in descriptive form.The results of the study show, to increase the role of BPK as the front line in eradicating corruption, it is necessary to take several strategic steps. BPK must reposition and strengthen the role of the State Financial Loss Calculation Report (LHP) as the main frame of reference in maximizing state financial recovery (Asset Recovery) due to corruption. will produce maximum results if there is no cooperation with various related parties, in this case Law Enforcement Officials. The KPK in preventing and eradicating corruption as well as PPATK in detecting indications of suspicious financial transactions certainly plays an important role in the legal process for criminal acts of corruption, while the BPK plays a role in increasing transparency and accountability of the public and business sectors.